1985
DOI: 10.1128/jcm.21.5.711-714.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a new, rapid enzyme-linked immunosorbent assay with latex particle agglutination for the detection of Haemophilus influenzae type b infections

Abstract: A new, rapid enzyme-linked immunosorbent assay (ELISA) for the detection of polyribosylribitol phosphate of Haemophilus influenzae type b was compared with a commercially available latex particle agglutination (LPA) system (Bactigen; Wampole Laboratories, Cranbury, N.J.). By adding specimens and the anti-poly-ribosyIribitol phosphate immunoglobulin-enzyme conjugate to the solid phase in a single step, it was possible to complete the ELISA procedure in 30 min. The ELISA was capable of detecting 0.3 ng of polyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Unfortunately, meningococcal antigen is sensitive to heat and, therefore, might not be detectable by LA after specimens have been heated to 100°C (160). Cross-reactions between a commercial H. influenzae LA reagent and S. pneumoniae, N. meningitidis group C, S. aureus, and Escherichia coli have been reported (84). In addition, urine can contain urethral flora that can cause false-positive results due to antigenic cross-reactions (44).…”
Section: Methods Of Detecting Bacterial Antigensmentioning
confidence: 99%
“…Unfortunately, meningococcal antigen is sensitive to heat and, therefore, might not be detectable by LA after specimens have been heated to 100°C (160). Cross-reactions between a commercial H. influenzae LA reagent and S. pneumoniae, N. meningitidis group C, S. aureus, and Escherichia coli have been reported (84). In addition, urine can contain urethral flora that can cause false-positive results due to antigenic cross-reactions (44).…”
Section: Methods Of Detecting Bacterial Antigensmentioning
confidence: 99%
“…Several factors, however, limit the clinical utility of bacterial antigen tests and make their routine use controversial. These factors include a decline in the incidence of Hib invasive disease following the advent of specific vaccination (35), imperfect antigen specificity (4,6,8,11,13,21,23,25,28,30,32), misleading positive results due to detection in urine or CSF of circulating Hib antigen after vaccination (7,15,36,43,44), contamination of urine with skin flora (3,40), and, importantly, the common failure of physicians to respond to rapidly generated diagnostic test results (26). In this review of over 5,000 LA tests, we found no evidence of clinical utility to support their current common use and instead found a high incidence of confounding results.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, no positive reactions were noted in CSF, serum, or urine specimens collected from children infected with bacteria other than H. influenzae type b or from children without evidence of bacterial infection, whereas on three occasions a false-positive reaction was the result of the LA test in three cases of infection with S. pneumoniae. Recently, Macone et al (19) reported that five patients infected with a pathogen other than H. influenzae serotype b had a positive Bactigen-LA test. These five cases were represented by S. pneumoniae type 14 (two cases), N. meningitidis group C (one case), E. coli K-100 (one case), and Staphylococcus aureus (one case).…”
Section: Discussionmentioning
confidence: 99%
“…With the commercial kit recommendations, one can find that heating the specimen at 80°C for 5 min is required to eliminate these inconclusive reactions. It was also reported that the use of polyclonal antibodies in the EIA system for the detection of H. influenzae type b antigens could yield a false-positive result (19,25). Such nonspecific reactions and methods to minimize them have been reviewed by Yolken (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation